EXPLORATORY STUDY OF WOMEN MANAGERS’S CAREER DEVELOPMENT IN MINING INDUSTRY: CHALLENGES, SUPPORT, AND STRATEGIES BEHIND IT - Sulthan Naufal Rabbani (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
The increase of women manager each year coexist with the low percentage compared to their male couneterparts caused by the challenges in their career development in the form of glass ceiling phenomenon, resulting in underrepresentative of women in strategic position in minings’s oil and gas company, which is a male dominated industry. This research explores the experiences of 6 women managers’s career advancement by conducting an in-depth interview. Using thematic analysis, this research found that women managers in oil and gas encounter challenges from their personal life and external matters, receive support from their partners and external side, and implement strategy relating to oneself and their external environment. This research also found the views regarding the figure of professional female workers in the mining industry are seen as the basis for female worker to compete in this industry. This research fills the gap in literature which discusses glass ceiling in male dominated industry, specifically in the perspective of women managers and their experience in career development process. The findings could serve as reference for employer in order to create gender-friendly and gender-neutral policy and to open many other possibilities for women in order to have an equal opportunity to serve in strategic positions.